1997
DOI: 10.1021/jp9713827
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Vapor Deposition of Silver on Plasma-Modified Polyurethane Surfaces

Abstract: The surface chemistry of [(1,1,1,2,2,3,3-heptafluoro-7,7-dimethyl-4,6-octanedionato)(trimethylphosphine)silver(I)], [(fod)AgP(CH 3 ) 3 ], a silver precursor for chemical vapor deposition (CVD), has been investigated on plasma-modified polyurethane surfaces by means of reflection−absorption infrared spectroscopy (RAIRS) and X-ray photoelectron spectroscopy (XPS). On the unmodified polyurethane surface, the RAIRS and XPS data show that [(fod)Ag(P(CH 3 ) 3 )] reacts with polyurethane CO, N−H, and C−O−C groups pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…It contains not only the formation of silver carboxylate but also the strong covalently bonding interactions between silver ions and the functional groups in PAA molecules. Scheme 4 shows what we believe (based on our FTIR, XPS data and literatures [31,[36][37][38][39]) are the most probable chemical entities formed during the ion exchange of PAA in silver ion solutions. Some of them might promote the formation of inter-or intra-molecular hydrogen-bonding [40] or might function as crosslinking points joining the macromolecules together to form the extended network and therefore make the silver-ion-doped PAA film undissolved in its original good solvent.…”
Section: Ion Exchange Reaction Of Paa With Silver Ionsmentioning
confidence: 79%
See 1 more Smart Citation
“…It contains not only the formation of silver carboxylate but also the strong covalently bonding interactions between silver ions and the functional groups in PAA molecules. Scheme 4 shows what we believe (based on our FTIR, XPS data and literatures [31,[36][37][38][39]) are the most probable chemical entities formed during the ion exchange of PAA in silver ion solutions. Some of them might promote the formation of inter-or intra-molecular hydrogen-bonding [40] or might function as crosslinking points joining the macromolecules together to form the extended network and therefore make the silver-ion-doped PAA film undissolved in its original good solvent.…”
Section: Ion Exchange Reaction Of Paa With Silver Ionsmentioning
confidence: 79%
“…3A. The peak at 533.6 eV is pertaining to the COOH species; the peak at 532.7 eV is associated with the oxygen atoms in the C-O bonds; and the peak at 531.4 eV is corresponding to the oxygen atoms in all carbonyl groups (C]O, COOH and CONH) [31][32][33]. However, following ion exchange, it can be clearly observed that an additional peak at 529.0 eV was present in the O 1s core-level spectra, as illustrated in Fig.…”
Section: Ion Exchange Reaction Of Paa With Silver Ionsmentioning
confidence: 99%
“…The maximum peak of nitrogen shifted to 400.3 from 400.5 eV after plasma treatment. This behavior could be explained as the new bond formation on the melt‐electrospun TPU surface by dissociation of the NH bond …”
Section: Resultsmentioning
confidence: 99%
“…For estimating this parameter for different samples, we need to measure the film thickness t . Table II shows the cross section due to the stretching vibration of CH from the literature [13,14]. In the table, the peaks at 3085 and 3010 cm −1 and the related vibrations are assigned to CH or CH 2 sp 2 bonding of olefin.…”
Section: Methodsmentioning
confidence: 99%